Interleukin-27 in Tuberculosis: A Sheep in Wolf’s Clothing? - Ritter, Kristina; Rousseau, Jasmin; Hölscher, Christoph (Frontiers in Immunology, 2022)
In tuberculosis (TB), protective inflammatory immune responses and the pathological sequelae of chronic inflammation significantly depends on a timely balance of cytokine expression. In contrast to other anti-inflammatory cytokines, interleukin (IL)-27 has fundamental effects in experimental Mycobacterium tuberculosis infection (Mtb): the absence of IL-27-mediated signaling promotes a better control of mycobacterial growth on the one hand side but also leads to a chronic hyperinflammation and immunopathology later during infection. Hence, in the context of novel host-directed therapeutic approaches for the management of TB, administration of antibiotics under IL-27 blockade may represent an advanced treatment option. In contrast, administration of IL-27 itself may allow to treat the immunopathological consequences of chronic TB. In both cases, a better knowledge of the cell type-specific and kinetic effects of IL-27 after Mtb infection is essential. This review summarizes IL-27-mediated mechanisms affecting protection and immunopathology in TB and discusses possible therapeutic applications.